The Potency of Giving Turmeric (Curcuma domestica Val.) Flour to The Quality of Quail (Coturnix coturnix japonica) Eggs - Astrid Annisya Adhy Putri; Agus Widodo; Ratna Damayanti; Tri Wahyu Suprayogi (Journal of Applied Veterinary Science And Technology, 2020)
Background: Supplementation of good feed on quail can improve its egg quality. One of the excellent supplement comes from herbs. Turmeric is one of the herbs which good for livestock because of its content, curcuminoid, and essential oil. Curcuminoid can increase quail egg yolk color, increase the appetite so that it can increase the weight of poultry. Purpose: To know the potential of giving turmeric flour to the quality of quail’s egg. Methods: The methods used 40 quails, divide into two groups. Groups P0: quail fed without turmeric flour, and group P1: quails fed with 1,07% turmeric fluor. Variables observed were egg weight, haugh unit, egg yolk index, white egg index, and yolk color. Result: The Egg weight, haugh unit, yolk index, and yolk color of P1 was higher than quails fed without turmeric. However, there was no difference between the egg whites index of both groups. Conclusion: The addition of turmeric on feed has the potential to increase the egg weight, haugh unit, yolk index, and yolk color. However, turmeric was not directly affected the formation of egg whites.